Investigation of curcumin-mediated signalling pathways in head and neck squamous cell carcinoma. (28th November 2017) - Nanjappa, Vishalakshi; Sathe, Gajanan J.; Jain, Ankit P.; Rajagopalan, Pavithra; Raja, Remya; Subbannayya, Tejaswini; Patil, Arun H.; Kumar, Prashant; Prasad, T. S. Keshava; Mathur, Premendu Prakash; Sidransky, David; Gowda, Harsha; et al.
Objectives: Curcumin has been shown to exhibit anti-neoplastic effects. However, due to its poor bioavailability, the use of curcumin as an anti-cancer drug is limited. Thus, it is necessary to identify molecules as an alternative to curcumin that could serve as anti-cancer targets. In this study, we attempted to understand the underlying curcumin-mediated signalling pathways contributing to anti-neoplastic effects of curcumin. Methods: We carried out mass spectrometry-based phosphoproteomic analysis of head and neck cancer cell line, CAL 27, treated with and without curcumin to identify curcumin-mediated signalling pathways. Serine/threonine kinases were enriched using titanium dioxide. Results: This resulted in the identification of 5921 phosphopeptides corresponding to 1878 proteins. Of these, 275 and 183 phosphopeptides corresponding to 335 and 242 proteins (≥2.0-fold) were found to be hyper- and hypo-phosphorylated, respectively, in response to curcumin treatment. Calcium/calmodulin-dependent protein kinase kinase 2 (CaMKK2), a serine/threonine kinase, and its downstream target protein kinase AMP-activated non-catalytic subunit beta 1 (PRKAB1) were found to be hypo-phosphorylated when treated with curcumin. Further, silencing or inhibiting CaMKK2 resulted in decreased invasion and colony forming ability of not only CAL 27 cells but also other head and neck squamous cell carcinoma (HNSCC) cell lines. Further, Western blot analysis showed that curcumin-mediated signalling is corroborated by CaMKK2. Conclusions: Taken together, our results suggest that CaMKK2 could be a novel therapeutic target in HNSCC and can serve as an alternative to curcumin.